Supporting Female Survivors of Gender-Based Violence Experiencing Homelessness: Outcomes of a Health Promotion Psychoeducation Group Intervention - Bani-Fatemi, Ali; Malta, Monica; Noble, Amanda; Wang, Wei; Rajakulendran, Thanara; Kahan, Deborah; Stergiopoulos, Vicky (Frontiers in Psychiatry, 2020)
Homelessness is an important risk factor for gender-based violence , particularly among youth, and disproportionally affects women and girls. Survivors of gender-based violence experience enduring and severe physical, psychological, and sexual health problems. Although key elements in service delivery for survivors of gender-based violence have been identified, little is known about outcomes of community-based programs aiming to assist homeless and unstably housed youth experiencing gender-based violence. This longitudinal study aimed to quantitatively evaluate changes in mental health and well being outcomes in female identified youth experiencing gender-based violence and homelessness, 12 months after enrolment in a community-based, trauma-informed, brief group psychoeducation intervention. Standardized survey measures were administered at baseline, 6 and 12 months for 70 participants, recruited between February 2017 and April 2019, assessing quality of life, psychological distress, traumatic symptoms, substance use, resilience, victimization, and sense of mastery. Linear mixed models were used to examine longitudinal changes in quality of life as well as secondary outcomes among study participants. After 12 months, quality of life increased significantly among participants (p=0.009), and the 12-month victimization score was significantly decreased relative to baseline (p=0.05). Changes in other outcomes were not statistically significant. Findings suggest that community-based brief group psycho-education interventions may be a promising approach to improving outcomes for this disadvantaged population.